An analysis of long-term trends in the abundance of domestic livestock and free-roaming dogs in the Bale Mountains National Park, Ethiopia - Vial, F; Sillero-Zubiri, C; Marino, J; Haydon, D; Macdonald, D (2011)
Livestock inside the Bale Mountains National Park poses a threat to the persistence of the Ethiopian wolf (Canis simensis) through grazing-induced habitat degradation and the transmission of diseases from the domestic dogs kept alongside the herds. We used a 21-year time series to explore long-term trends in the numbers of cattle, caprines and free-roaming domestic dogs in two core Ethiopian wolf areas (the Web valley and the Sanetti plateau) and to test whether seasonal variations in primary productivity underlies the current livestock production system. No trends in livestock numbers were detected in the Web valley, where livestock are most abundant and graze seasonally. Livestock numbers have increased significantly on most of the Sanetti plateau, grazing all year-round albeit at a lower intensity. Livestock use of the Web valley was positively correlated with vegetation productivity as derived from remotely sensed data, the Normalized Difference Vegetation Index (NDVI). On the Sanetti plateau, neither primary productivity nor livestock numbers showed signs of strong seasonality. The current livestock production system has the potential to degrade the vegetation that sustains the wolves' rodent prey while an increase in free-roaming domestic dogs in parts of their range may heighten the risk of disease transmission. +Résumé: Le bétail qui paît dans le Parc National des Bale Mountains est une menace pour la survie du loup éthiopien Canis simensis parce que le pâturage entraine une dégradation de l'habitat et favorise la transmission de maladies des chiens domestiques qui accompagnent les troupeaux. Nous avons utilisé une série de données couvrant 21 années pour étudier les tendances à long terme du nombre de bovins, de chèvres et de chiens domestiques parcourant librement deux zones clés pour les loups d'Ethiopie, la Vallée de Web et le Plateau de Sanetti, et pour tester si des variations saisonnières de productivité primaire sous-tendent le système actuel de production de bétail. Nous n'avons détecté aucune tendance dans le nombre de têtes de bétail dans la Vallée de Web, où le bétail est le plus abondant et où il paît de façon saisonnière. Le nombre de bêtes a augmenté significativement sur la plus grande partie du Plateau de Sanetti, où elles paissent toute l'année quoique à plus faible intensité. La fréquentation de la Vallée de Web était positivement liée à la productivité de la végétation selon des données recueillies à distance (NDVI). Sur le Plateau de Sanetti, ni la productivité primaire, ni le nombre de têtes de bétail ne présente de signe fort de saisonnalité. Le système actuel de production du bétail a le potentiel de dégrader la végétation permettant le maintien du rongeur qui est la proie du loup d'Ethiopie, cependant que la libre circulation des chiens domestiques dans plusieurs parties de leur aire de répartition pourrait accroître le risque de transmission de maladies. © 2010 Blackwell Publishing Ltd.